Islamic Boarding Schools (Pesantren) Innovation in Preventing Violence and Sexual Harassment: Case Study in The Special Region of Yogyakarta, Indonesia - Khozin, Muhammad; Saharuddin, Erni; Faidati, Nur; Sakir, Sakir (UUM Press, 2023)
In Indonesia, in addition to formal education, informal education is also known as pesantren. Pesantren is a place where people study Islam, explore the Qur’an and Sunnah of the Prophet and other worship. In addition to studying religious knowledge, it is not uncommon for pesantren to have collaborated with formal education. In Indonesia, pesantren is the choice for the community for the provision of educational services. Resident students are one of the main characteristics of pesantren. Unfortunately, this characteristic turns out to be the main cause of several cases of violence and sexual harassment in pesantren. The Indonesian National Commission for Women noted that during 2017-2021 there were 16 cases of sexual violence in pesantren. Meanwhile, BBC News reported that in early 2023 at least 4 cases had been revealed. This condition is very sad and makes pesantren have to improve themselves. How do pesantren innovate to prevent sexual violence and harassment? This study used a qualitative approach, data collection using literature study and deep interview techniques. In-depth interviews were conducted with 3 managers of large pesantren in the Special Region of Yogyakarta, Indonesia. The data were analysed through descriptive qualitative analysis. The results of the analysis show that to prevent violence and sexual harassment in pesantren, strengthening the joint commitment to protect each other between students, caregivers and managers is the main thing in the management of a pesantren.